Characteristic Outline of Head Trauma Patients at Dr. Saiful Anwar General Hospital - Laksono, Buyung Hartiyo; Pertiwi, Previasari Zahra; Siswagama, Taufiq Agus; Isngadi, Isngadi (Journal of Anaesthesia and Pain, 2025)
Background: Traumatic brain injury is defined as a decline in brain function characterized by a decreased level of consciousness, seizures, and focal sensory and motor neurologic deficits caused by blunt force or penetration by a sharp object into the intracranial space. This reseracrh aims to determine the characteristics of head trauma patients at Dr. Saiful Anwar General Hospital, Malang.Methods: This descriptive observational study sampled all head trauma patients at Dr. Saiful Anwar General Hospital, Malang, from March to August 2023. The study variables included patient demographics, cause of trauma, clinical data, pre-and postoperative procedures, outcomes of trauma patients undergoing treatment, and length of stay. Data were analyzed using Microsoft Excel.Results: A total of 227 head trauma patients were identified, most of whom were men aged 20-39 (71). Students (72) were the most common victims of head trauma, most often due to accidents. There were 156 patients with mild head injuries. 208 patients had normal oxygen saturation. 157 patients had normal hemoglobin, 181 patients had normal sodium, and 196 patients had normal blood glucose levels. 102 patients experienced hypocarbia. A normal CT scan of 141 patients was performed. 206 patients underwent surgery, while 214 patients did not undergo tracheostomy. 149 patients underwent surgery with early emergence. The highest number of patients were patients with a hospital stay of more than 14 days (140 patients). The most common outcome was mild disability (84 patients).Conclusion: Most patients were male, aged 20-39. The most common cause was accidents involving students. Most patients with mild head injuries had normal oxygen saturation, hemoglobin,sodium, and blood glucose levels. Most patients with hypocarbia had no bleeding, and CT scans showed no bleeding. Most patients underwent surgery and early emergence, with a hospital stay of more than 14 days, and the most common outcome was mild disability.